Comparing the Effectiveness of Two Intervention Methods Based on Education with Music Software and Visual Communication on Stereotyped Movements and Hand-Eye Coordination in Children with Autism - Azadeh Talebi; Leila Kashani Vahid Kashani Vahid; Maryam Asase; Gholam Ali Afrooz; Manouchehr Moradi Sabzevar (پژوهش‌های کاربردی روانشناختی)
This study aimed to evaluate the efficacy of two intervention methods based on education with music software and visual communication, in addressing stereotyped movements and hand-eye coordination in autistic children in Amol city. Applied research and quantitative data collection method (semi-experimental) were implemented with a pre-test-post-test and follow-up design. The research population was comprised of all minors diagnosed with autism disorder at the Khurshid Autism Center in Amol city in 2022. Randomly divided into three groups (2 experimental groups and 1 control group), the sample size was selected from 45 volunteers (24 males and 21 girls). The autism diagnostic questionnaire (GARS) and the motor-visual test (DTVP) were implemented. The video communication method (PECS) was implemented in six sessions, each lasting 30 minutes, and music software training was conducted in ten sessions. The data were subjected to multivariate covariance analysis and the LSD post hoc test using the spss24 software. The results indicated a distinction between the experimental groups and the control group. Treatment intervention programs demonstrated a positive outcome (P<0.05). The therapeutic interventions in the experimental groups remained stable after one month, as indicated by the results of the follow-up test. Music software training was demonstrated to be effective in enhancing the hand-eye coordination and stereotyped movements of autistic children. Consequently, its application in autistic individuals was justified.